Encouraging English Language Use through the “Desaku” Project - Rahmanti Asmarani; Juli Ratnawati (Institut Agama Islam Negeri Palopo, 2020)
“Desaku”, is an encouragement project which is held in Dian Nuswantoro University. The research is aimed at describing the activity of the project dealing with the strategies of learning process and the motivation of the participants. The descriptive survey research was designed by preparing the questionnaires provided 15 closed questions. The population of the survey are the academic staff and administrative staff of Dian Nuswantoro University as participants of the program. Determination of the number of samples applied the convenience sampling technique. 60 respondents were selected based on the criteria that they had participated as participants in ”Desaku” project for at least one year and were actively involved. The analysis of the data collected is conducted through statistic descriptive using the percentages (%) then it is presented in the form of chart. Each chart had been structured according to its respective fields, and the frequency and percentage used to analyze and describe the results. The results of the research showed that 91% of the participants enjoyed the program and felt happy with the program. 85% of the participants agree that the various strategies have been applied to encourage the staffs to practice English orally.